The impact of globalization on the transport sector: The case of Tunisia - Derbel, Ahmed; Souiai, Torkia; Samet, Kaies (Asian Economic and Financial Review, 2024)
This paper aims to present the theoretical and practical aspects of the impact of globalization on the transport sector in Tunisia. Nowadays, globalization affects the transport sector, making it more dynamic. In this respect, most studies, both internationally and in Tunisia, have focused on maritime transport as it is the mode of transport that is most affected by the globalization phenomenon. Therefore, to expand on these observations, we carried out an econometric study in Tunisia covering the 1976–2016 period based on the error correction model. The findings confirm some of the previous observations and show that international trade, which represents globalization, has the greatest impact on national transport, both in the short and long runs. Therefore, this study suggests that if our country wants to promote the transport sector, it should meet the challenges of globalization through greater economic openness and an environment conducive to foreign direct investment.